Pengembangan Sistem Informasi Komunitas Pengamatan Burung Berbasis Web - Sukma, Ina Desirra; Adithama, Stephanie Pamela; Julianto, Eddy (Universitas Atma Jaya Yogyakarta, 2024)
The bird-watching community has activities to record and manage observation data. So far, important observational data has only been written in personal notes. These notes have the potential to be lost and not even published. This method, which is still done manually, must be more consistent in detailed information shared with various bird-watching communities. To solve this problem, it is necessary to develop a website-based bird observation community information system to make it easier for admins to manage bird data and for bird watchers to manage observation data. The information system was developed using the PHP programming language with the help of the Laravel framework and using the Bootstrap framework to implement the program code developed. A website-based bird observation community information system has been successfully developed and used to make it easier for admins to manage bird data and manage observation data. Based on the results of the system evaluation by users, overall users were satisfied using the bird watching community information system that was built. Komunitas pengamatan burung memiliki kegiatan mencatat dan mengelola data pengamatan. Data penting pengamatan tersebut selama ini hanya tertulis dalam catatan pribadi. Catatan tersebut berpotensi hilang bahkan tidak terpublikasi. Cara yang masih dilakukan secara manual tersebut menyebabkan kurangnya konsistensi detail informasi yang dibagikan ke berbagai komunitas pengamatan burung. Sebagai penyelesaian masalah tersebut, perlu dikembangkan sistem informasi komunitas pengamatan burung berbasis website yang digunakan untuk memudahkan admin melakukan pengelolaan data burung serta memudahkan para pengamat burung melakukan pengelolaan data pengamatan. Sistem informasi dikembangkan menggunakan bahasa pemrograman PHP dengan bantuan framework Laravel dan menggunakan framework Bootstrap untuk implementasi kode program yang dikembangkan. Sistem informasi komunitas pengamatan burung berbasis website berhasil dikembangkan dan digunakan untuk memudahkan admin melakukan pengelolaan data burung dan pengelolaan data pengamatan. Berdasarkan hasil evaluasi sistem oleh para pengguna, secara keseluruhan pengguna sudah merasa puas menggunakan sistem informasi komunitas pengamatan burung yang dibangun.